MODIFIKASI SECARA HEAT MOISTURE TREATMENT PADA PATI UBI JALAR UNGU UNTUK PANGAN FUNGSIONAL - Tanak, Yolivia (JSTT, 2016)
Food diversification efforts by leveraging local food, such as purple sweet potato (Ipomoea batatas Blackie) needs to be improved because of the potential to be used as a functional food ingredient. Purple Sweet Potato Starch Modification function to change the functional properties contained in starch to increase the added value as functional food ingredients. This study uses a modification Heat Moisture Treatment (HMT) on purple sweet potato starch with the treatment temperature and heating times. The study design used completely randomized design (CRD) arranged as factorial with two factors, namely by heating starch at high temperatures (70oC, 85oC and 100°C) and prolonged heating (3 hours, 5 hours and 7 hours). Data were analyzed using analysis of variance (ANOVA) followed by a further test HSD (α = 0.05). The results showed that the treatment temperature and longer heating HMT give real effect to the Oil Holding Capacity, moisture content, FT-IR, starch content, fiber content and antioxidant activity, but to the Water Holding Capacity and digestibility no significant effect. Judging from the functional value best treatment is prolonged heating temperature of 85ºC with 3 hours resulted in digestibility of 8.50%, temperature 70°C with a 3 hour long heating produces antioxidant activity of 18.79%, and prolonged heating temperature of 100ºC with 5 hours produce high levels of fiber 1,39%.